A Cross Sectional Study to Assess Certain Determinants Co-Related with Anaemia in Pregnant Women Attending Antenatal Clinic at Rural Health Training Centre in Western Maharashtra - Langare, Sanjivani D; Rajderkar, S S; Naik, J D; Patil, Vishwanath (National Journal of Community Medicine, 2013)
Context: In India, anaemia is a common cause of maternal morbidity and mortality and a key factor related to low birth weight. As per NFHS-3 (2005-6) survey in rural Maharashtra 58% pregnant women are anaemic. It indicates the problem of anaemia among pregnant women in rural area and need of research in this context. Aim: To assess certain determinants co-related with anaemia in pregnant women. Settings and Design: It was a cross sectional study conducted at Rural Health Training Centre in Western Maharashtra, India. Methods and Material: A total of 213 pregnant women registered during 1st Jan 2010 to 30th June 2010 were included in present study. Hemoglobin estimation was done by Sahli’s method during her first antenatal visit in 12-20 weeks of gestational age. Data was collected using pre-designed, pretested proforma. Statistical analysis used: The results were analyzed using the SPSS v16. Statistical methods used were mean and chi square test. Results: The overall prevalence of anaemia was found to be 88.26%. The prevalence of anaemia was 59.05% among antenatal women who were in the age group of 20-25 years. Higher prevalence of anaemia was seen among women who had high parity, spacing less than 1 year and from low socioeconomic status. Conclusions: Anaemia continues to be a problem with the existing health care resources. Socio-economic status, literacy of women, parity and spacing of children are the major determinants that contribute to the problem of anaemia.